In vivo Realization of Dual Photodynamic and Photothermal Therapy for Melanoma by Mitochondria Targeting Dinuclear Ruthenium Complexes under Civil Infrared Low‐power Laser - Wang, Meng‐Fan; Yang, Rong; Tang, Shi‐Jie; Deng, Yu‐Ang; Li, Guo‐Kui; Zhang, Dan; Chen, Daomei; Ren, Xiaoxia; Gao, Feng (Angewandte Chemie International Edition, 2022)
A series of dinuclear RuII complexes with extremely high TPA cross sections in the range of 800–900 nm have been designed. The amphiphilic complex Ru3 containing tert‐butyl groups has balanced performance in singlet oxygen generation and photothermal conversion and becomes the ideal drug candidate of the series. Ru3 targets mitochondria without penetrating the nucleus, which substantially increases its photodynamic therapy activity and reduces its dark cytotoxicity. Ru3 successfully suppresses melanoma tumor growth in vitro and in vivo with combined photodynamic and photothermal therapy under low light dose irradiation of an 808 nm low‐power laser, avoiding the known PDT resistance in melanoma. The excellent therapeutic effect of Ru3 facilitates its applications in further human trials for larger or deeper buried tumors, thereby becoming a prospective candidate for a new generation of low‐power IR‐driven dual PDT/PTT drugs. Dinuclear ruthenium complexes with high two‐photon absorption in the IR region and photothermal conversion efficiency have been developed to target mitochondria without penetrating the nucleus for tumor therapy. They show suppressed melanoma tumor growth in vitro and in vivo with dual two‐photon photodynamic and photothermal therapy.